The Structure of Student Engagement in Community College Student Success Programs: A Quantitative Activity Systems Analysis - Deryl K. Hatch (SAGE Publishing, 2017)
Community colleges increasingly implement various student success programs, including 1st-year seminars, college skills courses, learning communities, and orientation, in an effort to boost degree completion. However, it is unclear how success programs' curricular designs may contribute to these and associated student outcomes. Such inquiry is limited, in part, by the lack of methodological frameworks for program impact heterogeneity research. This study proposes a new conceptualization of nominally different student success programs as instances of a broader activity, which also provides a way to operationalize their curricular structures in comparable ways. Second, to briefly illustrate this approach, the study leverages matched program and student data to investigate how variations in student engagement-an emergent intermediate outcome for fostering successful college going-are related to variation in program design. Findings reveal that structural and underutilized curricular elements may be more impactful than skills-based curricula that are typically the organizing focus of these programs.